RELATIONSHIP BETWEEN THE END OF THE VEGETATION PERIOD AND FRUIT PROPERTIES IN THE WALNUT POPULATION - Paunović, Svetlana (Journal of Agricultural Sciences (Belgrade), 2023)
The main objective of the study was to examine the walnut population from the region of Eastern Serbia for determining the relationship between the end of the vegetation period and fruit properties (fruit weight, kernel content, oil and raw protein content). Walnut trees showed highly significant differences in the tested parameters. The walnut population was dominated by trees with a medium end time of the vegetation, moderate resistance to low temperatures (39.5%) and very small fruits (23.5%). The fruits of these trees had а high kernel content (15.8%) and a moderate oil and raw protein content (25.8% and 38.3%, respectively). Contrary, in the walnut population there were the fewest trees of late ending of the vegetation, with extremely large fruits (0.1%), exceptional kernel content (0.2%) and pronouncedly high oil and raw proteins content (0.18% and 0.5%, respectively). The studied walnut trees show a great variability in the date of end of vegetation and fruit properties, which indicates a high potential of the population in the selection of new genotypes, and the necessity for their conservation towards further breeding, propagation and commercial cultivation.
Keywords: Juglans regia L., end of the vegetation season, fruit characteristics